1996
DOI: 10.1093/plankt/18.8.1503
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-flow cytometric identification and enumeration of the ichthyotoxic dinoflagellate Gyrodinium aureolum Hulburt in artificially mixed algal populations

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…Our studies demonstrated that the use of chlorophyll fluorescence in conjunction with an antibody probe allows a population to be identified and sorted, but accurate enumeration was not achieved. As reported by Vrieling et al (1995) for Gyrodinium aureolum, we encountered significant cell loss during processing of samples for flow cytometric analysis. We determined that there are direct cell losses associated with the incubations and wash steps, but also found that inaccurate cell counts occurred because larger cells (e.g., A. fundyense) would partially block the flow cytometer sample tubing.…”
Section: Immunofluorescence and Flow Cytometrymentioning
confidence: 55%
See 4 more Smart Citations
“…Our studies demonstrated that the use of chlorophyll fluorescence in conjunction with an antibody probe allows a population to be identified and sorted, but accurate enumeration was not achieved. As reported by Vrieling et al (1995) for Gyrodinium aureolum, we encountered significant cell loss during processing of samples for flow cytometric analysis. We determined that there are direct cell losses associated with the incubations and wash steps, but also found that inaccurate cell counts occurred because larger cells (e.g., A. fundyense) would partially block the flow cytometer sample tubing.…”
Section: Immunofluorescence and Flow Cytometrymentioning
confidence: 55%
“…Vrieling et al 1994 andVrieling et al 1995). In this study we provide an evaluation of two antibody-based approaches to the isolation, enumeration, separation and biochemical analysis of a target species -the toxic dinoflagellate Alexandrium fundyense -in natural plankton samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations